Castleman’s Disease Presenting as a Parotid Mass in the Pediatric Population: A Report of 2 Cases - Sean W. Delaney; Shengmei Zhou; Dennis Maceri (Case Reports in Otolaryngology)
Introduction. Angiofollicular lymph node hyperplasia (Castleman’s disease) is a nonmalignant lymphoproliferative disorder that generally involves the lymph nodes of young adults, most commonly in the mediastinum. Rarely, Castleman’s disease may present in the parotid gland. The disease can be further classified into unicentric or multicentric forms, with considerable differences in presentation, treatment, and prognosis. Case(s). We present cases of two pediatric patients, aged 7 and 11, who both presented with a slow-growing, painless parotid mass. In each case, the mass was excised via a superficial parotidectomy and the diagnosis made postoperatively upon further pathologic examination. At 6 months of follow-up, both had fully intact facial nerve function and no evidence of recurrence. Discussion. Castleman’s disease presents a diagnostic challenge in the head and neck region, as radiographic characteristics and fine needle aspiration results are often inconclusive. Definitive diagnosis requires surgical excision for pathologic examination. The unicentric form generally presents as a painless mass and can be successfully treated with complete excision. The multicentric form is associated with constitutional symptoms and its treatment remains controversial. Conclusion. Although rare, clinicians should be aware of both forms of Castleman’s disease when creating a differential diagnosis for parotid masses.